A μ4‐Oxo Bridged Tetranuclear Zinc Complex as an Efficient Multitask Catalyst for CO2 Conversion. Issue 11 (24th February 2021) - Kumar, Raman; Sahoo, Subash C.; Nanda, Prasant K.
Abstract: A tetranuclear zinc complex having formula [Zn4 (L)4 ( μ2 ‐OH2 )2 ( μ4 ‐O)]⋅2TEAH⋅DMF⋅4H2 O (1 ) has been synthesized from a benzothiazole based schiff base ligand. The complex was characterized by various spectroscopic and analytical techniques along with single crystal X‐ray diffraction (SCXRD) study. The crystal structure of the complex reveals that, there is formation of a tetranuclear dianionic core having metal centers in distorted trigonal bipyramidal (TBP) geometry supported by a μ4 ‐oxo and two μ2 ‐aqua bridgings. The μ 4 ‐oxo acquires a special position, connecting to the zinc centers in a distorted tetrahedral ( Td ) fashion is mainly responsible for the higher nuclearity of the complex. The complex 1 exhibited multitask catalytic ability for CO2 utilization. It acts as an efficient catalyst for the conversion of various epoxides to cyclic carbonates as well as mimics carbonic anhydrase (CA) metalloenzyme. Hydrolysis of para‐ nitrophenyl acetate ( p‐ NPA) was used as a model reaction to evaluate the CA activity. The complex also catalyzes the formation of bicarbonate (HCO3 − ) from CO2 by converting CaCl2 to CaCO3 . Abstract : A μ4 ‐ oxo and μ2 ‐ aqua bridged tetranuclear zinc complex was successfully synthesized and characterized. The complex shows good thermal and kinetic stability can be prepared in bulk with phase purity. The complex shows multitasking catalytic ability towards CO2 conversion and utilization as well as it acts as a mimicking model system for the carbonic anhydrase metalloenzyme. It also shows excellent catalytic efficacy, and very good reusability towards the catalytic process.